Awareness of muslim consumer toward halal foods / Maslia Md Zain - Md Zain, Maslia (Faculty of Business and Management, 2018)
Nowadays, there are variety of foods that are available in Malaysia. However, Muslims are obliged to consume halal foods and beverages. They are not allowed to consume haram foods due to prohibition in Islam and it already mentioned in Quran. There is an evidence in Surah Al-Baqarah, which Allah allow Muslims to eat everything that are lawful and good and we must avoid those that are prohibited. Muslim know about it but they are not applied it in their daily life. There are issues of food packaging that do not meet halal package standard, revocation of halal certificate due to hygiene violation and use of the ingredients that are not permitted by Islam are become concern towards Muslim consumers. This research aims to study the awareness of halal foods among Muslim consumers in Shah Alam, Selangor. This research is based on data obtained from survey questionnaire that conducted in area Shah Alam, Selangor. The data was analysed to evaluate and determine on how Muslim consumers aware with availability of halal foods around them. The research suggested that awareness of Muslim consumers are linked to the food outlets preference, understanding of halal concept, attitude toward halal food and self identity of the Muslim itself. The researcher use pilot test,SPSS, Cronbatch alpha, Correlation as method in this study. The results of the study reveal that food outlets preference and understanding of halal concept is insignificant and the attitude toward halal food and self identity is significant with the awareness of halal foods among Muslim consumers.